Perspectives on oxy-fuel combustion for supercritical CO2 direct-fired power cycle - Francesco Di Sabatino; Brian J. Connolly; Owen M. Pryor; Steve H. White (Applications in Energy and Combustion Science)
This paper explores the potential of oxy-fuel direct-fired supercritical carbon dioxide (sCO2) power cycles, proposing them as a promising strategy towards achieving near-total carbon capture while utilizing existing fossil fuels. It offers insights into the future of CO2- and sCO2-diluted combustion science and combustor design, supported by a review of the current state of the art. The paper is divided into four sections: chemical kinetics and the development of chemical mechanisms, numerical simulations tools, combustion and laser ignition experimental efforts, and the current state of the art and perspectives of combustor design efforts. The paper underscores the need for additional experimental measurements to validate chemical mechanisms, numerical simulations, and combustor design to advance understanding of CO2 and sCO2-diluted combustion science. The authors advocate for increased collaboration within the scientific community and the development of standardized lab-scale burners and combustor geometries to facilitate comparison and validation as well as reduce development costs. The paper emphasizes that significant research and development efforts are crucial to ensuring the safety, reliability, and efficiency of CO2 and sCO2-diluted combustion processes and combustor design. The knowledge and strategies applicable to conventional gas turbines may not directly transfer to sCO2 cycles, necessitating dedicated research efforts to advance this promising technology towards widespread adoption.